2022
DOI: 10.1002/adsc.202200541
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐Catalyzed Oxidative Carboamination of Maleimides with Amines and α‐Bromo Carboxylates

Abstract: A copper-catalyzed oxidative carboamination of maleimides with alkyl amines and α-bromo carboxylates is described. These multicomponent reactions show good functional group compatibility and are suitable for the late-stage modification of a series of neuroprotective agents, providing a direct path for the library synthesis of 3-carbo-4-amino maleimides. The initial copper-catalyzed oxidative amination of maleimides with amines to form enamines intermediate, followed by copper-catalyzed radical alkylation with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Importantly, the use of alkyltin fluoride as a novel and appealing alkylation reagent is an excellent addition to alkyl halides as free radical precursors. 7 The rapid nucleophilic substitution between primary alkyl halides and alkylamines makes the three-component carboamination of maleimides impossible. Therefore, our study provides a complementary strategy for the introduction of alkyl chains into maleimides.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the use of alkyltin fluoride as a novel and appealing alkylation reagent is an excellent addition to alkyl halides as free radical precursors. 7 The rapid nucleophilic substitution between primary alkyl halides and alkylamines makes the three-component carboamination of maleimides impossible. Therefore, our study provides a complementary strategy for the introduction of alkyl chains into maleimides.…”
Section: Introductionmentioning
confidence: 99%
“…Indium organometallics have also been utilized to generate 3, 4‐disubstituted maleimides from their halide precursors [42] . A copper‐catalysed oxidative carboamination of maleimides with amines and α‐bromo carboxylates has been reported at 120 °C in presence of potassium benzoate and oxygen [43] …”
Section: Introductionmentioning
confidence: 99%
“…[42] A copper-catalysed oxidative carboamination of maleimides with amines and α-bromo carboxylates has been reported at 120 °C in presence of potassium benzoate and oxygen. [43] 1, 4-quinones are also interesting motifs found in natural products, within materials with unique electronic and visual properties, as building blocks in synthetic chemistry and among natural and synthetic dyes and pigments (Scheme 1a). [44][45][46][47][48][49][50][51][52][53][54] Various CÀ C bond formation reactions that works on α, β-unsaturated carbonyls (viz.…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 ] In this context, we reported that α‐bromoesters, a tertiary alkyl precursor, could react smoothly with electron‐deficient maleimides and alkylamines in the presence of a copper salts. [ 4 ] Due to the stability of the alkyl radical and the matching of the stepwise reaction rate, this method is limited to the introduction of tertiary carbon and has no effect on secondary and primary carbon. Despite these incontrovertible footstones, the pre‐preparation of raw materials and the use of precious transition‐metal catalysts in many cases with regard to derivative the drug molecules remain a great challenge.…”
Section: Introductionmentioning
confidence: 99%